Case Study : Lily Sdn Bhd / Intan Najihah Mohamad Napiah - Mohamad Napiah, Intan Najihah (2020)
Lily has produced ready-made umbrella, custom-made umbrella, car sunshade, sky dance and inflatable couch. At, LILY SDN BHD., they have provided a comprehensive service from manufacturing umbrellas to the modification of their existing umbrellas to suit consumers’ requirements. They will assist the consumers in proposing the most cost effective and impressive designs to create values in promotional strategy. Their product related services include the following; manufacturer of customized Umbrella design and functionality, customizing or modifications of existing Ready-Made umbrellas, printings on Umbrella panels, printing and customization of oriental umbrellas and printing on Sunshades, Grin bags, Sky dancers and other innovative products.